Kekerasan permukaan email setelah aplikasi gel karbamid peroksida 10% dan pasta buah strawberry - Pambudi Santoso T; Devi Rianti; Asti Meizarini (Journal of Dentomaxillofacial Science, 2009)
he influence of strawberries as bleaching alternative material toward surfacemicrohardness of the teeth is still unknown so that a research should be conducted toquantitatively assess the effects of bleaching with 10% carbamide peroxide andblended strawberry paste on post-extracted incisive teeth by performing superficialmicrohardness analysis. Three groups of sample i.e. group 1 (control): post-extractedincisive teeth soaked in ordinary mineral water, group 2: soaked in carbamideperoxide 10% gel, and group 3: soaked in 100% strawberry paste. The microhardessof each sample group is tested before and after the application of bleaching materials.The result was there was significant difference of strawberry paste compared to CP10% gel and mineral water soaked incisive teeth. The data obtained are tabulated,then analyzed with one way Anova and LSD. It can be concluded that the applicationof carbamide peroxide 10% gel in 6 weeks doesn’t decrease the microhardness ofteeth enamel surface. However, the application of strawberry paste decreases themicrohardness of enamel surface.